2017
DOI: 10.1039/c7ra04036a
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of polyepoxysuccinic acid as a novel draw solution in the forward osmosis process

Abstract: Polyepoxysuccinic acid (PESA) is a green corrosion scale inhibitor. When PESA is used for wastewater desalination in the forward osmosis (FO) process, the diluted PESA solution could be used for cooling systems. In our investigation, the effects of membrane orientation, temperature and flow rate on FO performance are studied using PESA as a draw solute. The results show that the effect of temperature on water flux is obvious, but the water flux increase is higher from 25 C to 35 C than that from 35 C to 45 C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 48 publications
3
14
0
Order By: Relevance
“…When compared to other experiments utilizing inorganic fertilizers, the observed flux is much lower than that of inorganic DS using the same type of membrane adopted by Nasr and Sewilam ( 2015 ). However, comparing the obtained results with other organic DS shows a good agreement with the experimental results by Wang et al ( 2017 ) who used a tailor-made TFC membrane, and the results obtained by Alaswad et al ( 2018 ) who used a nanofiltration membrane (TFC-SR2) in FS-AL mode for investigating the performance of sucrose and glucose as draw solutions against deionized water in a forward osmosis (FO). In another comparison with the obtained results using other organic draw solutions as presented in Islam et al (2019), the reported flux is higher due to higher osmotic pressure differences between feed and draw solutions.…”
Section: Resultssupporting
confidence: 85%
“…When compared to other experiments utilizing inorganic fertilizers, the observed flux is much lower than that of inorganic DS using the same type of membrane adopted by Nasr and Sewilam ( 2015 ). However, comparing the obtained results with other organic DS shows a good agreement with the experimental results by Wang et al ( 2017 ) who used a tailor-made TFC membrane, and the results obtained by Alaswad et al ( 2018 ) who used a nanofiltration membrane (TFC-SR2) in FS-AL mode for investigating the performance of sucrose and glucose as draw solutions against deionized water in a forward osmosis (FO). In another comparison with the obtained results using other organic draw solutions as presented in Islam et al (2019), the reported flux is higher due to higher osmotic pressure differences between feed and draw solutions.…”
Section: Resultssupporting
confidence: 85%
“…In the beginning, water flux is higher because it increases with an increase in the osmotic potential of the DS (Figure 5a). This is due to the fact that as DS concentration increases, a larger osmotic driving force is generated, which leads to a higher water flux across the membrane (Chakrabortty et al, 2015; Wang et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Polyepoxysuccinic acid (PESA), a green water treatment agent, has become a research hotspot because of its excellent scale inhibition against calcium carbonate and corrosion inhibition. However, it exhibits very poor properties of inhibiting calcium phosphate and dispersing iron oxide. To improve the abilities of inhibiting calcium phosphate and dispersing iron oxide, a sulfonic acid group was introduced into the molecular structure. Domestic and foreign scholars have synthesized modified polyepoxysuccinic acid polymers by adding monomers containing a sulfonic acid group, such as 2-acrylamido-2-methylpropanesulfonic acid (AMPS), sodium styrene sulfonate (SS), and sodium allyl sulfonate (SAS).…”
Section: Introductionmentioning
confidence: 99%